Chemically peculiar A and F stars with enhanced s-process and iron-peak elements: stellar radiative acceleration at work - Xiang, Mao-Sheng; Rix, Hans-Walter; Ting, Yuan-Sen; Ludwig, Hans-Günter; Coronado Martínez, Johanna Carolina Andrea; Zhang, Meng; Zhang, Hua-Wei; Buder, Sven; Dal Tio, Piero (The astrophysical journal, 2020)
We present greater than or similar to 15,000 metal-rich ([Fe/H] > -0.2 dex) A and F stars whose surface abundances deviate strongly from solar abundance ratios and cannot plausibly reflect their birth material composition. These stars are identified by their high [Ba/Fe] abundance ratios ([Ba/Fe] > 1.0 dex) in the LAMOST DR5 spectra analyzed by Xiang et al. They are almost exclusively main-sequence and subgiant stars with T-eff greater than or similar to 6300 K. Their distribution in the Kiel diagram (T-eff-log g) traces a sharp border at low temperatures along a roughly fixed-mass trajectory (around 1.4M(circle dot)) that corresponds to an upper limit in convective envelope mass fraction of around 10(-4). Most of these stars exhibit distinctly enhanced abundances of iron-peak elements (Cr, Mn, Fe, Ni) but depleted abundances of Mg and Ca. Rotational velocity measurements from GALAH DR2 show that the majority of these stars rotate slower than typical stars in an equivalent temperature range. These characteristics suggest that they are related to the so-called Am/Fm stars. Their abundance patterns are qualitatively consistent with the predictions of stellar evolution models that incorporate radiative acceleration, suggesting they are a consequence of stellar internal evolution, particularly involving the competition between gravitational settling and radiative acceleration. These peculiar stars constitute 40% of the whole population of stars with mass above 1.5M(circle dot), affirming that "peculiar" photospheric abundances due to stellar evolution effects are a ubiquitous phenomenon for these intermediate-mass stars. This large sample of Ba-enhanced, chemically peculiar A/F stars with individual element abundances provides the statistics to test more stringently the mechanisms that alter the surface abundances in stars with radiative envelopes.
Gesehen am 28.10.2020